2009
DOI: 10.1074/jbc.m109.026195
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: TcJAMYC: A bHLH transcription factor that activates paclitaxel biosynthetic pathway genes in yew

Abstract: Abstract:Paclitaxel (Taxol ®) is a highly modified diterpene anti-cancer agent produced by the gymnosperm Taxus. Taxus suspension cell cultures have the potential to provide a sustainable source of paclitaxel, but the paclitaxel biosynthetic pathway is not fully characterized, making metabolic engineering efforts difficult. Methyl jasmonate (MJ) is used to elicit paclitaxel production in suspension cultures. Here we show that the promoters of five genes encoding enzymes of the paclitaxel biosynthetic pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This cis-acting element is usually located in the promoter of genes involved in multiple physiological pathways. Nims et al (2009) found that the yew bHLH TcJAMYC can bind to the E-box in the promotor of paclitaxel-related genes to activate their transcriptional expression. Huang et al (2013) demonstrated that the Poncirus trifoliata PtrbHLH can bind to an E-box in the promoter region of the POD gene.…”
Section: Bhlhs Selectively Bind To Particular Cis-acting Elements Of Target Genesmentioning
confidence: 99%
“…This cis-acting element is usually located in the promoter of genes involved in multiple physiological pathways. Nims et al (2009) found that the yew bHLH TcJAMYC can bind to the E-box in the promotor of paclitaxel-related genes to activate their transcriptional expression. Huang et al (2013) demonstrated that the Poncirus trifoliata PtrbHLH can bind to an E-box in the promoter region of the POD gene.…”
Section: Bhlhs Selectively Bind To Particular Cis-acting Elements Of Target Genesmentioning
confidence: 99%